An outline of the genesis and transformation of medical schools in the Kielce region, 1945–2014 - Zaczek-Kucharska, Ewa; Zawierucha, Elżbieta; Kozieł, Dorota (Medical Studies/Studia Medyczne, 2019)
The research presents the history of the establishment and transformation of medical schools over the years 1945–2014 in the Kielce region. After the Second World War, a lamentable situation transpired in the region regarding the numbers of adequately qualified mid-level medical personnel. The establishment and development of new medical schools was aimed at addressing the dearth of staff and, as a result, improving care and raising health standards in society. The 1960s and 1970s were a period of relative stability in the education of mid-level medical personnel. Relevant principles of medical education were developed and implemented. A Polish model to educate future medical service employees was developed. Changes to the political system during the 1980s resulted in economic and political difficulties for the country, which influenced the development of medical education. Evaluation of mid-level educational practices in Poland revealed that they were closely related to teaching tendencies in Europe.